THE CONCEPTUAL FIELD OF PHILOSOPHIZING IN CONDITIONS OF GLOBALIZATION - Антіпова, О. П. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The article is devoted to the study of the main tendencies in transformation of the conceptual field of philosophizing in conditions of globalization processes typical for modern society.